The Effects of Increasing the Capacity of Admission in Emergency Ward in increasing the Rate of Patient Acceptance at the Time of Crisis - S Geravandi; F Soltani; MJ Mohammadi; Sh Salmanzadeh; S Shirali; A Shahriari; SH Beytmashal; Z Aslani (Armaghane Danesh Bimonthly Journal, 2016)
Background & Aim: The emergency ward at the time of a disaster is the most important ward for providing therapy service to the injured. The purpose of this research study was to study of the effects of increasing the capacity of admission in emergency ward in increasing the rate of patient acceptance at the time of crisis at Razi Educational Hospital, Ahvaz, Iran.